The Effect of the Food For Baby & Kids Application on the Nutritional Status of Babies Aged 6-12 Months - Lukyta Pratika Dewi; Shinta Alifiana Rahmawati (Journal of Health Sciences, 2025)
The global incidence of stunting in 2020 was 149.2 million children under the age of 5 who were stunted, 45.4 million children were underweight, 38.9 million children were overweight in the world, and in Indonesia it was 21.6%. One of the factors causing stunting is the lack of appropriate feeding during complementary foods for breast milk due to the mother's lack of knowledge and skills regarding complementary foods for breast milk. Food For Baby & Kids (FFBK) is a web-based e-Health innovation idea as an complementary foods for breast milk information guide. This study aims to determine the effect of the FFBK application on the nutritional status of babies aged 6-12 months. This research method is a quasi-experimental research with a One Group Pretest-Posttest Design. Samples were taken based on purposive sampling technique, as many as 15 mothers of babies aged 6-12 months. The instruments used were the FFBK application and questionnaire. The data analysis used was univariate analysis and bivariate analysis using the Paired Sample t-Test. The research results showed significant differences in the nutritional status of babies before and after using the FFBK application. The mean nutritional status before (-0.533) increased to (-0.208). The results of statistical tests using the Paired Sample t-Test showed a p-value of 0.002 for nutritional status. The research conclusion is that there is an influence of the FFBK application on the nutritional status of babies aged 6-12 months. It is hoped that mothers can use the FFBK application as a source of information and can apply it in their daily lives.